2010
DOI: 10.1186/1471-2474-11-117
|View full text |Cite
|
Sign up to set email alerts
|

Histological and ultrastructural evaluation of the early healing of the lateral collateral ligament epiligament tissue in a rat knee model

Abstract: BackgroundIn this study, we evaluated the changes which occurred in the epiligament, an enveloping tissue of the ligament, during the ligament healing. We assessed the association of epiligament elements that could be involved in ligament healing.MethodsThirty-two 8-month old male Wistar rats were used in this study. In twenty-four of them the lateral collateral ligament of the knee joint was surgically transected and was allowed to heal spontaneously. The evaluation of the epiligament healing included light m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
54
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(58 citation statements)
references
References 16 publications
3
54
0
1
Order By: Relevance
“…Single or rarely small groups of collagen fibers arranged chaotically, did not reveal a well-presented recovery of the EL. Wellpresented immunostaining for collagen type I and III (current results, Figure 7) and weak immunopositive reaction for collagen type V was detected at 8 day after healing throughout the MCL EL scar [10,30]. Light microscopy research on the sixteenth day after injury showed similar features as in previous period, but the granulation margins in the EL were less distinct and the area of scar formation appeared to be more organized (Figure 8).…”
Section: El Role During Ligament Healing (Light Electron Microscopicsupporting
confidence: 56%
See 4 more Smart Citations
“…Single or rarely small groups of collagen fibers arranged chaotically, did not reveal a well-presented recovery of the EL. Wellpresented immunostaining for collagen type I and III (current results, Figure 7) and weak immunopositive reaction for collagen type V was detected at 8 day after healing throughout the MCL EL scar [10,30]. Light microscopy research on the sixteenth day after injury showed similar features as in previous period, but the granulation margins in the EL were less distinct and the area of scar formation appeared to be more organized (Figure 8).…”
Section: El Role During Ligament Healing (Light Electron Microscopicsupporting
confidence: 56%
“…The latter compose the ligament scar tissue and are mostly responsible for the collagen fibers synthesis. According to Georgiev et al [9,10] …”
Section: Types Of Cells (Light Electron Microscopy)mentioning
confidence: 99%
See 3 more Smart Citations